Pengaruh Locus of Control terhadap Perencanaan Karir Siswa: Kajian Literatur Sistematis - Apriliana, Yona; F, Firman; N, Netrawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Career planning is mature is important in the aspect of individual development, especially students who are learning the secondary school. One psychological factor that influences career planning is the locus of control. Students with high Locus of Control have the belief that success or failure in achieving something is determined by their own abilities and efforts, not based on luck or gifts of others. This belief in self encourages students to be more active, independent and responsible in planning their career steps. This article discusses the effect of Locus of Control on student career planning, as well as the urgency of the development of locus of control in order to support career planning.